Investigación de baar en tuberculosis pulmonar a través de cultivo como diagnóstico precoz para el tratamiento de los pacientes que acuden al hospital “José María Velasco Ibarra”, de la ciudad del tena durante el periodo de diciembre 2014 a mayo 2015. - Salcán Pilatuña, Erika Nataly (2015)
This research work proposed by the method of Ogawa Kudoh determine pulmonary tuberculosis, this being who is a legitimate public health problem both nationally and globally. Its importance is determined mainly by its high morbidity and mortality, for purposes of this paper is structured in Chapter I approach the problem so it is worth pausing to analyze your current epidemiological situation, further its objectives by which proposes analyze the cost benefit of Ogawa Kudoh technique, to determine the incidence of the number of patients during the period December 2014 to May 2015. in Chapter II a theoretical framework where knowledge of Pulmonary Tuberculosis expand and everything related to it based on scientific knowledge, the technique for this research is described. In Chapter III the methodological framework which is used the scientific method is a process to explain phenomena, establishing relationships between the facts and state laws, principles that explain physical phenomena. In Chapter IV Analysis and interpretation of results with data that were collected from 107 patients attending the hospital José María Velazco Ibarra city of Tena during the period established which were expressed in frequencies and percentages and plotted in tables and pastry